Cajal bodies in neurons. Issue 6 (3rd June 2017) - Lafarga, Miguel; Tapia, Olga; Romero, Ana M.; Berciano, Maria T.
ABSTRACT: Cajal is commonly regarded as the father of modern neuroscience in recognition of his fundamental work on the structure of the nervous system. But Cajal also made seminal contributions to the knowledge of nuclear structure in the early 1900s, including the discovery of the "accessory body" later renamed "Cajal body" (CB). This important nuclear structure has emerged as a center for the assembly of ribonucleoproteins (RNPs) required for splicing, ribosome biogenesis and telomere maintenance. The modern era of CB research started in the 1990s with the discovery of coilin, now known as a scaffold protein of CBs, and specific probes for small nuclear RNAs (snRNAs). In this review, we summarize what we have learned in the recent decades concerning CBs in post-mitotic neurons, thereby ruling out dynamic changes in CB functions during the cell cycle. We show that CBs are particularly prominent in neurons, where they frequently associate with the nucleolus. Neuronal CBs are transcription-dependent nuclear organelles. Indeed, their number dynamically accommodates to support the high neuronal demand for splicing and ribosome biogenesis required for sustaining metabolic and bioelectrical activity. Mature neurons have canonical CBs enriched in coilin, survival motor neuron protein and snRNPs. Disruption and loss of neuronal CBs associate with severe neuronal dysfunctions in several neurological disorders such as motor neuron diseases. In particular, CB depletion in motor neurons seems to reflect a perturbation of transcription and splicing in spinal muscular atrophy, the most common genetic cause of infant mortality.